2021
DOI: 10.1002/rth2.12527
|View full text |Cite
|
Sign up to set email alerts
|

Micronized purified flavonoid fraction for the treatment of chronic venous insufficiency, with a focus on postthrombotic syndrome: A narrative review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
2
0
4
Order By: Relevance
“…The beneficial effects of different flavonoids in cardiovascular complications of diabetes have been studied in experimental models of T1D and T2D [ 18 , 23 , 25 , 44 ]. Micronized purified flavonoid fractions containing phlebotonic drugs such as diosmin and hidrosmin have been used in the treatment of chronic venous insufficiency likely because of its ability to ameliorate venous tone and contractility [ 21 , 45 ]. However, to our knowledge this is the first study evaluating in relevant preclinical models the effects of hidrosmin on the vascular dysfunction associated with hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of different flavonoids in cardiovascular complications of diabetes have been studied in experimental models of T1D and T2D [ 18 , 23 , 25 , 44 ]. Micronized purified flavonoid fractions containing phlebotonic drugs such as diosmin and hidrosmin have been used in the treatment of chronic venous insufficiency likely because of its ability to ameliorate venous tone and contractility [ 21 , 45 ]. However, to our knowledge this is the first study evaluating in relevant preclinical models the effects of hidrosmin on the vascular dysfunction associated with hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Улучшение микроциркуляторного русла положительно сказывается на оксигенации тканей, что было доказано при проведении чрескожной оксиметрии у пациентов с ХВН. Было зарегистрировано увеличение скорости эритроцитов в капиллярах по сравнению с исходным уровнем, что в свою очередь уменьшило капиллярный застой и улучшило венозную микроангиопатию [32,34].…”
Section: доказательная эффективность микронизированной очищенной фрак...unclassified
“…Отличий в частоте возникновения побочных реакций в зависимости от препарата не было выявлено, и их возникновение объясняется длительной продолжительностью лечения (более 6 мес.) [34,40].…”
Section: доказательная эффективность микронизированной очищенной фрак...unclassified
“…These antioxidants protect endothelial cells from hypoxia and inflammation, have affinity for venous endothelium and in clinical studies were found to reduce markers of endothelial damage and dysfunction [54][55][56][57]. Flavonoids, in particular modified variants rutoside and micronized purified flavonoid fraction (MPFF), were found to reduce symptoms in both primary CVD and PTS [58,59]. Guidelines recommend its use in treatment of primary CVD [60], and a large trial is ongoing to confirm its effectiveness on reducing symptoms of PTS (NCT03833024).…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%